Orientalism as a Device of Violence: Representation and Subordination in the Construction of Alterity - López Angelini, Martín Ricardo (Razón y fe, 2025)
In this article, we examine the interrelations between orientalism and violence, proposing a reconceptualization of the former as a “device”. Through a critique and expansion of Said’s notions of the term, we analyze the multiple facets of Orientalism as a conceptual and epistemic device intrinsic to the human experience that establishes and (re)configures both hierarchies and cultural subordinations. We argue that orientalism entails an inherent conceptual violence, unfolding in various stages where it manifests in different forms. Thus, the proposed reconceptualization enables the visualization of the power dynamics underlying the discursive construction of a horizon of “Orient(s)” as well as the instrumentalization of these categories in specific historical and political contexts. Finally, we emphasize the utility of such tool in unveiling and confronting the underlying violences embedded in representations of alterity through an economy of violence.